Luteolin and luteolin-7-O-glucoside inhibit lipopolysaccharide-induced inflammatory responses through modulation of NF-κB/AP-1/PI3K-Akt signaling cascades in RAW 264.7 cells - Park, C.M., Dong-Eui University, Busan, Republic of Korea; Song, Y.S., Inje University, Gimhae, Republic of Korea (Nutrition research and practice, 2013)
Luteolin is a flavonoid found in abundance in celery, green pepper, and dandelions. Previous studies have shown that luteolin is an anti-inflammatory and anti-oxidative agent. In this study, the anti-inflammatory capacity of luteolin and one of its glycosidic forms, luteolin-7-O-glucoside, were compared and their molecular mechanisms of action were analyzed. In lipopolysaccharide (LPS)-activated RAW 264.7 cells, luteolin more potently inhibited the production of nitric oxide (NO) and prostaglandin E2 as well as the expression of their corresponding enzymes (inducible NO synthase (iNOS) and cyclooxygenase-2 (COX-2) than luteolin-7-O-glucoside. The molecular mechanisms underlying these effects were investigated to determine whether the inflammatory response was related to the transcription factors, nuclear factor (NF)-κB and activator protein (AP)-1, or their upstream signaling molecules, mitogen-activated protein kinases (MAPKs) and phosphoinositide 3-kinase (PI3K). Luteolin attenuated the activation of both transcription factors, NF-κB and AP-1, while luteolin-7-O-glucoside only impeded NF-κB activation. However, both flavonoids inhibited Akt phosphorylation in a dose-dependent manner. Consequently, luteolin more potently ameliorated LPS-induced inflammation than luteolin-7-O-glucoside, which might be attributed to the differentially activated NF-κB/AP-1/PI3K-Akt pathway in RAW 264.7 cells.